2011
DOI: 10.1177/1545968311401628
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Analysis of Head, Trunk, and Pelvis Movement When People Early After Stroke Reach Sideways

Abstract: Lateral reaching to the unaffected side early after stroke revealed a different pattern than normal and patients reached less far and moved at a slower speed. Specific training strategies to improve reaching are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 19 publications
(19 reference statements)
1
23
0
Order By: Relevance
“…These specific modulations in COG dynamics in the rising on tiptoes and lateral reaching imagery are indicative of some correspondence between postural adjustments during actual performance and those observed during motor imagery: rising on tiptoes execution is accompanied by a striking reduction in the base of support, large forward-backward displacement of the COG (Nardone and Schieppati, 1988) and greater COG variability (2–6-fold higher than both reaching execution tasks); accordingly, execution of lateral reaching movements requires a large lateral trunk motion (Verheyden et al, 2011) and COP displacement (Brauer et al, 1999), along with a large increase in lateral COG variability (~2-fold higher than rising on tiptoes and forward reaching task). Comparing this COG dynamics pattern with that evoked during motor imagery, we suggest the existence of some execution-imagery “postural correspondence.”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These specific modulations in COG dynamics in the rising on tiptoes and lateral reaching imagery are indicative of some correspondence between postural adjustments during actual performance and those observed during motor imagery: rising on tiptoes execution is accompanied by a striking reduction in the base of support, large forward-backward displacement of the COG (Nardone and Schieppati, 1988) and greater COG variability (2–6-fold higher than both reaching execution tasks); accordingly, execution of lateral reaching movements requires a large lateral trunk motion (Verheyden et al, 2011) and COP displacement (Brauer et al, 1999), along with a large increase in lateral COG variability (~2-fold higher than rising on tiptoes and forward reaching task). Comparing this COG dynamics pattern with that evoked during motor imagery, we suggest the existence of some execution-imagery “postural correspondence.”…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of postural adjustments preceding or following movement is usually dependent of the action characteristics. For example, during the execution of a rise on tiptoe movement, a significant forward-backward motion of the body center of gravity can be observed (Nardone and Schieppati, 1988); likewise, when a subject is instructed to “reach sideward as far as possible,” large lateral trunk motion is required (Verheyden et al, 2011) and increases in lateral center of pressure (COP) displacement occurs (Brauer et al, 1999). Although there is some suggestive evidence that motor imagery modulates postural sway in a task-dependent manner (Rodrigues et al, 2003, 2010; Grangeon et al, 2011; Boulton and Mitra, 2013) this issue remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the circumduction gait includes a combination of hiking and forward rotation of the pelvis [6]. These evidences highlighted that the sway amplitude and stability of pelvis are important in paretic patients, and could have an influence on circumduction gait pattern of lower limb and locomotor performance, as well as functional ability of upper limb activity and trunk control of stroke patients [7][8][9]. These studies emphasized the impact of pelvis on motor function and gait.…”
Section: Y Mao Et Al / Changes Of Pelvis Control With Subacute Strokementioning
confidence: 99%
“…Few studies have investigated the movement of the spine and pelvis separately. Verheyden et al reported on pelvic movement during lateral reach movements in the sitting position [36], and Messier et al described the movements of the upper trunk and pelvis when subjects touched a target placed in front of them with the forehead [37]. To execute the sit-to-stand movement smoothly, the pelvis must be leaned forward to flex the hip joint, and the trunk must be flexed in order to: (1) use the hip extension moment; (2) reduce the knee extension moment; and (3) project the center of gravity within the base of support [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%